Repurposing pinacol esters of boronic acids for tuning viscoelastic properties of glucose-responsive polymer hydrogels: effects on insulin release kinetics. Issue 37 (19th May 2022) - Ali, Akbar; Nouseen, Shaista; Saroj, Saroj; Shegane, Meenakshi; Majumder, Priyankar; Puri, Aarti; Rakshit, Tatini; Manna, Debasish; Pal, Suchetan
Abstract : Injectable hydrogels capable of releasing the desired amount of insulin under hyperglycemic conditions will significantly advance smart insulin development. We report glucose-responsive hydrogels with programmable insulin release properties. Abstract : In the era of the diabetes pandemic, injectable hydrogels (HGs) capable of releasing the desired amount of insulin under hyperglycemic conditions will significantly advance smart insulin development. Several smart boronic acid-based polymer HGs release insulin under high-glucose conditions. However, the correlation of insulin release characteristics with rheological properties is not well understood yet. Herein, we report a generalized and facile fabrication strategy of a new class of glucose-responsive hydrogels by crosslinking a biocompatible polymer, poly(vinyl alcohol) with pinacol esters of bisboronic acids via transesterification reactions. We show the versatility of the method by fabricating four hydrogels with diverse rheological properties. The HGs embody more than 70% water amenable for hosting insulin in the matrix. HG with high storage modulus, derived from 1, 4-benzenediboronic acid bis(pinacol) ester releases ∼3 fold less insulin compared to softer HGs derived from acetylene-1, 2-diyl bis(boronic acid pinacol ester) and bis[(pinacolato)boryl]methane under hyperglycemic conditions. We find that HG derived from the bis[(pinacolato)boryl]methane crosslinker exhibits superior insulin release properties due to the softness of the hydrogel matrix. We further show that the newly formulated gel is injectable without any structural change in the released insulin molecules and does not cause cytotoxicity. We believe that glucose-responsive hydrogels with tunable viscoelastic properties will pave the way for developing a variety of hydrogels with programmable insulin release properties.